2019
DOI: 10.3233/mnm-180265
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omega-3 supplementation on glycemic indices and lipid profile in type 2 diabetic patients with non-alcoholic fatty liver disease: A double-blind, randomized, clinical trial

Abstract: INTRODUCTION: Serum phospholipid omega-3 fatty acid levels in patients suffering from both type 2 diabetes (T2DM) and non-alcoholic fatty liver (NAFLD) are lower than in their healthy counterparts. Omega-3 supplementation can be effective in controlling glycemic indices in T2DM, and in improving lipid profiles in T2DM and NAFLD as well. The aim of this study was to evaluate the effects of omega-3 fatty acid supplementation on glycemic control and lipid profile in patients with T2DM and NAFLD. METHODS: In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The study of Dasarathy et al [ 24 ] reported that omega-3 supplementation has no effect on serum concentrations of TC, LDL-c and HDL-c. In addition, our original study demonstrated that omega-3 supplementation for 12 weeks reduced serum TG levels, but could not improve serum concentrations of TC, LDL-c and HDL-c in diabetic patients with NAFLD [ 26 ]. Moreover, the study of Scorletti et al [ 41 ] demonstrated that after intervention for 15–18 months, there is no significant difference between the omega-3 group (4 g/d) and the placebo group in levels of TC, LDL-c and HDL-c.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study of Dasarathy et al [ 24 ] reported that omega-3 supplementation has no effect on serum concentrations of TC, LDL-c and HDL-c. In addition, our original study demonstrated that omega-3 supplementation for 12 weeks reduced serum TG levels, but could not improve serum concentrations of TC, LDL-c and HDL-c in diabetic patients with NAFLD [ 26 ]. Moreover, the study of Scorletti et al [ 41 ] demonstrated that after intervention for 15–18 months, there is no significant difference between the omega-3 group (4 g/d) and the placebo group in levels of TC, LDL-c and HDL-c.…”
Section: Discussionmentioning
confidence: 99%
“…It seems, 2–4 g/d omega-3 has a beneficial effect on TG, but not TC, LDL-c and HDL-c. Omega-3 by inducing β-oxidation, decreasing VLDL synthesis, regulating gene expression of sterol-regulatory element-binding protein-1 (SREBP-1) and carbohydrate response element binding protein (ChREBP), modulating the TG synthesis, activating phosphatidic acid, diacylglycerol acyltransferase as well as LPL, and reducing the TG clearance from circulating VLDL particles can regulate serum TG [ 17 , 21 , 44 46 ]. To follow the principals of ethics in research, we clarify that our research group reported the effect of omega-3 fatty acids on fatty liver, visceral adiposity index, insulin resistance, body composition and lipid profile, previously [ 26 , 47 ]. We used the same data for the present article.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations